2015
DOI: 10.1007/s00221-015-4392-8
|View full text |Cite
|
Sign up to set email alerts
|

Audio-visual synchrony and feature-selective attention co-amplify early visual processing

Abstract: 2 ABSTRACT Our brain relies on neural mechanisms of selective attention and converging sensory processing to efficiently cope with rich and unceasing multisensory inputs. One prominent assumption holds that audio-visual synchrony can act as a strong attractor for spatial attention. Here, we tested for a similar effect of audio-visual synchrony on feature-selective attention. We presented two superimposedGabor patches that differed in colour and orientation. On each trial participants were cued to selectively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
3
17
0
1
Order By: Relevance
“…SSR power decreased with increasing stimulus presentation rate (main effect SSR component : F(2,22) = 55.76, P GG < 0.001, ε GG = 0.90, η 2 = 0.301; also see Figure 3 ) as has been documented extensively before (Keitel and Müller, 2015; Porcu et al, 2014). Figure 3c underlines that amplitudes further varied with the allocation of attention towards stimuli (main effect attention : F(1,11) = 24.15, P < 0.001, η 2 = 0.094) and were affected by audio-visual synchrony (F(1,11) = 71.01, P < 0.001, η 2 = 0.067).…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…SSR power decreased with increasing stimulus presentation rate (main effect SSR component : F(2,22) = 55.76, P GG < 0.001, ε GG = 0.90, η 2 = 0.301; also see Figure 3 ) as has been documented extensively before (Keitel and Müller, 2015; Porcu et al, 2014). Figure 3c underlines that amplitudes further varied with the allocation of attention towards stimuli (main effect attention : F(1,11) = 24.15, P < 0.001, η 2 = 0.094) and were affected by audio-visual synchrony (F(1,11) = 71.01, P < 0.001, η 2 = 0.067).…”
Section: Resultssupporting
confidence: 74%
“…In contrast to attentional gain, results of an earlier investigation suggested that synchrony-related gain effects may be specific to pulsation-driven SSRs. Using a paradigm similar to the present study, Keitel and Müller (2015) found that an SSR component with a frequency of twice the pulsation rate was exclusively susceptible to synchrony-related gain effects. At this rate, the stimulation presumably contained strong transients critical for establishing audio-visual synchrony (Werner and Noppeney, 2011).…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations